2019
DOI: 10.1149/2.1391912jes
|View full text |Cite
|
Sign up to set email alerts
|

Cathode/Electrolyte Interface-Dependent Changes in Stress and Strain in Lithium Iron Phosphate Composite Cathodes

Abstract: Dynamic interactions between electrode and electrolyte species during electrochemical cycling have an impact on the interfacial kinetics and mechanical stability of the electrode materials. In this study, we employ in-situ stress and strain measurements to investigate potential-dependent mechanical changes in lithium iron phosphate (LiFePO 4 ) cathodes during cyclic voltammetry in LiPF 6 and LiClO 4 -containing electrolytes. Analysis of the stress and strain derivatives in LiClO 4 -containing electrolytes exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 105 publications
0
21
0
Order By: Relevance
“…To better understand nanoscale structural changes in the electrode during charge and discharge cycles, capacity and strain derivatives with respect to voltage were calculated to investigate the charge behavior and physical response of the FePO 4 electrode during K intercalation. Previous studies on graphite, 18,20 lithium manganese oxide (LMO), 19,28,29 lithium iron phosphate (LFP), 30 and sodium iron phosphate (NFP) 23 electrodes showed that the evolution of the strain derivatives with potential closely matches with the phase transformations in the electrode structure. In these studies, the location of the strain derivative peaks was in good agreement with the evolution of the electrochemical response of the materials associated with the nanoscale changes in their structure.…”
mentioning
confidence: 96%
“…To better understand nanoscale structural changes in the electrode during charge and discharge cycles, capacity and strain derivatives with respect to voltage were calculated to investigate the charge behavior and physical response of the FePO 4 electrode during K intercalation. Previous studies on graphite, 18,20 lithium manganese oxide (LMO), 19,28,29 lithium iron phosphate (LFP), 30 and sodium iron phosphate (NFP) 23 electrodes showed that the evolution of the strain derivatives with potential closely matches with the phase transformations in the electrode structure. In these studies, the location of the strain derivative peaks was in good agreement with the evolution of the electrochemical response of the materials associated with the nanoscale changes in their structure.…”
mentioning
confidence: 96%
“…Broader current peak indicates the greater surface resistance towards the electrochemical reactions at the electrode / electrolyte interface. 49 The associated mechanical behavior of the electrode during cyclic voltammetry is shown in Fig 2 B and D, respectively. Strain values were set to zero at the beginning of each lithiation and delithiation cycle in order to compare mechanical deformations in each charge / discharge process.…”
Section: Probing Mechanical Deformations In Lifepo4 Cathodes In Diffe...mentioning
confidence: 99%
“…Previous studies showed CEI/SEI layer formation on the electrode surface which mostly causes additional resistance in batteries. 49,51,52 Electrochemical impedance spectroscopy (EIS) analyses were performed at different voltage values from 3.5 to 4.4 V during the first charge. Fig.…”
Section: Probing Mechanical Deformations In Lifepo4 Cathodes In Diffe...mentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand nanoscale structural changes in the electrode during charge and discharge cycles, capacity and strain derivatives with respect to voltage were calculated to investigate the charge behavior and physical response of the FePO4 electrode during K intercalation. Previous studies on graphite 15,24 , lithium manganese oxide (LMO) [25][26][27] , lithium iron phosphate (LFP) 28 and sodium iron phosphate (NFP) 21 electrodes showed that the evolution of the strain derivatives with potential closely matches with the phase transformations in the electrode structure. In the studies, the location of the strain derivative peaks was in good agreement with evolution of the electrochemical response of the materials associated with the nanoscale changes in their structure.…”
Section: Introductionmentioning
confidence: 99%